2019
DOI: 10.1002/ca.23396
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Fat in the Upper Eyelids of Asians: Application to Blepharoplasty

Abstract: The Asian eyelid has distinctive anatomical properties. Although the upper eyelid is reported in the literature to have no subcutaneous fat layer, we have often noticed adipose tissue below the upper eyelid skin during ophthalmic plastic surgeries. The aim of the present study was to examine the anatomical and histological features of subcutaneous adipose tissue in Asian upper eyelids using biopsies and microscopic morphological analysis. A total of 30 Chinese patients (60 upper eyelids) undergoing upper bleph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It is easy to observe the color difference between SF aspirated from the abdomen and OF resected from the eyelid. We and others also reported that the adipocytes of SF are bigger in size than those of OF. , These phenomena raise an interesting question. Are there any intrinsic differences in lipid composition between adipocytes of OF and SF?…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…It is easy to observe the color difference between SF aspirated from the abdomen and OF resected from the eyelid. We and others also reported that the adipocytes of SF are bigger in size than those of OF. , These phenomena raise an interesting question. Are there any intrinsic differences in lipid composition between adipocytes of OF and SF?…”
Section: Introductionmentioning
confidence: 78%
“…We and others also reported that the adipocytes of SF are bigger in size than those of OF. 2 , 3 These phenomena raise an interesting question. Are there any intrinsic differences in lipid composition between adipocytes of OF and SF?…”
Section: Introductionmentioning
confidence: 99%
“…The Asian eyelid has distinctive anatomical properties, including single eyelids, short tarsal plates, thick skin, weak levator function, and more fatty pads in the upper eyelid. Therefore, different and innovative surgical techniques are needed for Asian patients (16,17); however, few reports about the surgical methods are available for severe trachoma-induced UCE in Chinese patients.…”
Section: Discussionmentioning
confidence: 99%